A vaccine targeting lung resident-memory CD4+ T cell phenotype protects against Mycobacterium tuberculosis in mice - Kwang Hyun Ko; Seung-Hun Baek; Hyun Shik Bae; Young Mi Kim; Sun Hwa Gu; Yu Yeon Jung; Eun Hye Kwak; Han-Gyu Choi; Hwa-Jung Kim; Tae Sun Shim; Dong-Ho Kim; Seung Bin Cha (npj Vaccines)
Abstract Lung-resident memory T (TRM) cells respond rapidly and effectively to respiratory pathogen invasion, suppressing pathogen proliferation. Previously, we identified a defined TLR3 agonist called Nexavant (NVT) and developed a vaccine platform that utilizes it to induce lung TRM. In this study, we aimed to determine whether the protective effect of TRM cells is observed in tuberculosis (TB), a chronic bacterial respiratory disease. We synthesized a peptide vaccine by elongating the CD4+ T cell epitopes from Mycobacterium tuberculosis antigens ESAT-6, CFP-10, and HspX, adjuvanted it with NVT and administered the vaccine intranasally or intramuscularly to mice. We demonstrated that intranasal administration of an NVT-formulated peptide vaccine induced the generation of CD4+ TRM cells in the lungs, and that our vaccine platform, containing a limited number of CD4 epitopes, provided protective efficacy comparable to that of the BCG vaccine, which contains multiple T cell epitopes. Furthermore, the peptides used in the vaccine were reactive in 23 out of 24 (95.8%) human PBMCs, indicating that they contain promiscuous epitopes. Our results suggest a straightforward approach to controlling pulmonary TB more effectively through the induction of lung CD4+ TRM cells, even when using the same target antigen. Additionally, this study supports a theoretical basis for developing an inhalable TB vaccine using synthetic peptides.